Humanities-Based Educational Preparation and Empathy in Novice Nurses: Critical Thinking and Analytic Practice. Issue 1 (9th January 2023) - Adams, Sara B.; Scott, Linda D.
Abstract: Empathy has been associated with improved patient outcomes in practicing nurses, but empathy levels have been shown to decline in nursing students with increased clinical exposure. Integrating content from the humanities in the nursing classroom, not common in nursing education, supports professional empathy development and maintenance. Whether competencies gained from humanities-based liberal education courses support empathy in nursing students as they emerge into practice is not known. The purpose of this quantitative, nonexperimental, descriptive, pilot research was to explore the relationship between humanities-based liberal education and empathy in recently graduated, baccalaureate-prepared practicing nurses ( n = 40).